The Violations of Conversational Maxims By The Characters In Fast And Furious 1 Movie - Wahyu Unggul Widodo (Journalistics: Journal of English Teaching and Applied Linguistics, 2021)
This research discusses violating conversational maxim found in a movie entitled Fast and Furious 1 movie. This research has two main purposes which are finding the types of violating conversational maxim in that movie and explaining why the violations appears. The writer uses the theory of cooperative principle by Grice (1975). The source of this research is Fast and Furious 1 movie. In completing this research, the writer applies data collection method with an uninvolved conservation observation technique and analytical method with sorting determinants technique. The result of this research found that violating conversational maxim occurs when speaker does not fulfil a proper maxim during conversation to make certain meaning and is the discovery of all types of violating maxim purposed by Grice (1975). The analysis found 3 violations maxim of quantity, 9 violations maxim of quality, and 2 violations maxim of relation